(untitled) (Research, Society and Development, 2021)
Cassava (Manihot esculenta Crantz) is a crop of great economic, social and cultural importance, a source of work and income for family farmers. Pará is the largest producer of cassava, however, for the productive potential of the species, production in the state is low, which may be associated with low technological levels, less integration and actions of institutions and technical assistance offered to small farmers. Knowledge about the particularities, difficulties experienced by producers in municipalities that have the production of culture as an economic base, is seen as an essential point for achieving regional rural development. The objective was to develop the characterization of the potentials and limitations of the cassava production system in the city of São Francisco do Pará, a microregion in the northeast of Pará, through field research with an exploratory perspective and a quanti-quantitative approach, using the technique “snowball sampling” and use of questionnaires. It was found that the production of cassava is the main source of income and subsistence, with a predominance of low technological level, such as felling and burning. A lack of technical assistance from government agencies was identified. The main problems during the production process were the infrastructure of the “flour houses” and the transport factor during the commercial stage of the flour. There is a demand for greater public action, offering public policies, technical assistance, articulations that enable the entry of producers into markets, and thus the achievement of better financial results, moving towards greater local and regional development.